L-shaped association of low-density lipoprotein cholesterol with all-cause and cardiovascular mortality in cancer survivors: a population-based cohort study - Hou, Bowen; Hu, Yali; Wang, Hairong; Zhang, Huang; Gao, Xingyu; Cui, Ying; Zhao, Yilin; Xie, Jing; Yu, Xiaomei; Wang, Lang; Jiang, Hong; Zhu, Lihua (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesTo evaluate the association between LDL-C levels and all-cause, cardiovascular, and cancer mortality in cancer survivors, and to identify the LDL-C level associated with the lowest mortality risk, using data from NHANES 1999–2018.Study designPopulation-based cohort study.MethodsWe analyzed 1,958 U.S. cancer survivors from the National Health and Nutrition Examination Survey (NHANES) 1999–2018. We used Cox and Fine-Gray model to compare mortality risks across LDL-C quartiles, combined with restricted cubic spline analysis to assess nonlinear relationships, and piecewise linear regression to identify LDL-C inflection points.ResultsDuring a median follow-up of 7.3 years (681 deaths were recorded), we observed a nonlinear association between LDL-C levels and all-cause/cardiovascular mortality, wherein low levels of LDL-C were associated with an increased mortality risk. The identified optimal LDL-C thresholds were 119 mg/dl for all-cause mortality and 124 mg/dl for cardiovascular mortality. Age and CVD history influenced the association, with a negative linear relationship between LDL-C and all-cause mortality observed in individuals aged under 65 years and those in the primary CVD prevention.ConclusionsCancer survivors with low LDL-C levels were correlated with elevated all-cause and CVD mortality risks, particularly in younger patients and those without prior CVD.